Regular Solution Theory Model Used To Predict Supercritical CO2 Extraction Of p-chlorophenol Contaminate From Water Stream. - Kassim, K. M.; Zainal, A.; Davarnejad, R (2007)

(untitled)
The objective of this paper is the assessments of the feasibility of the extraction process utilizing a near critical carbon dioxide solvent with p-chlorophenol contaminate solute, which would be speeded up if it were possible to predict mutual solubility data.